Learning Path: Steering Agile Architecture Fundamentals - Gîrba, Tudor (O'Reilly Media, Inc., 2017)
How can you steer architecture towards a cohesive result in projects developed using Agile methodology? This Learning Path answers that question and others, as it introduces the concept of steering Agile architecture.